Enhanced photocatalytic activity of nanostructured Fe doped CeO2 for hydrogen production under visible light irradiation. (24th August 2016) - Mansingh, S.; Padhi, D.K.; Parida, K.M.
Abstract: A series of Fe-doped CeO2 nanoparticles were synthesised by simple co-precipitation technique by varying the dopant concentration (0 ≥ 5%) for photocatalytic water decomposition under visible light irradiation. The prepared photocatalysts were characterized by crystallographic, microscopic and spectroscopic methods to investigate the cause of their robust photocatalytic activity. XRD pattern suggest the formation highly crystalline face-centered cubic-fluorite structure of as-synthesized nanoparticles. The doping amount of Fe in CeO2 lattice strongly affects the bandgap tuning of neat CeO2 (CF0) from UV to Visible region i.e. 3.0eV–1.85 eV. The successful doping of Fe in CeO2 lattice resulted in the formation new dopant energy levels that facilitates interfacial charge transfer of both electron (e − ) and hole (h + ) for better photoredox reaction of water under visible light irradiation. Further, BET surface area measurement, PL, TRPL and photoelectrochemical analysis reveals that, presence of Fe 3+ ion in ceria lattice causes an enhancement of surface area, low PL intensity, longer average decay time (value of 〈 τ 〉 for CF0 and CF3 is 2.13 and 4.16 ns, respectively) and high photocurrent generation. The CF3 sample exhibits 31 times more current generation than CF0 and showed highest amount of hydrogen production i.e. 641 μmol/h with an apparent conversion efficiency of 9.13%. Graphical abstract: Highlights: A novel approach has been made to fabricate nanostructured Fe-doped CeO2 photocatalyst by simple co-precipitation method. Doping of Fe in CeO2 lattice strongly affects the band gap of neat CeO2 from UV to Visible region i.e. 3.0 eV–1.85 eV. Doping of Fe in CeO2 lattice resulted in dopant band that facilitates interfacial charge transfer and water redox reaction. Only 3 wt% Fe doping shows best H2 production activity under visible light irradiation and better photostability. The best sample (3 wt% doping) shows 31 times more photocurrent generation than neat CeO2 .